1983
DOI: 10.1139/f83-065
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Acidification of Some Nova Scotian Rivers and Its Impact on Atlantic Salmon, Salmo solar

Abstract: 1983. Evidence of acidification sf some Nova Scotian rivers and its impact on Atlantic salmon, Salmo snlar. Can. J. Fish. Aquat. Sci. 40: 462-473.River pH's in Nova Scotia are closely reIated to geology, and seasonal pH variation is well correlated with river discharge rates. In the geologically sensitive areas (granite and metamorphic rocks), river pH's have fallen significantly over the past 27 yr at an apparent average rate of 0.017 pH units/year. Concomitant with this decrease are a decline in HCOi concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 5 publications
0
38
0
1
Order By: Relevance
“…Chronic (year-round) acidification and its associated aluminum (Al) toxicity is a known cause of Atlantic salmon population decline in Norway (Hesthagen, 1989) and Nova Scotia (Watt et al, 1983). Recent studies have suggested that episodic acidification (single or re-occurring episodes lasting several days) may also have effects on Atlantic salmon populations in regions of the northeastern United States including Maine, where several salmon rivers have been listed as endan-gered (Magee et al, 2001(Magee et al, , 2003; National Academy of Science, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic (year-round) acidification and its associated aluminum (Al) toxicity is a known cause of Atlantic salmon population decline in Norway (Hesthagen, 1989) and Nova Scotia (Watt et al, 1983). Recent studies have suggested that episodic acidification (single or re-occurring episodes lasting several days) may also have effects on Atlantic salmon populations in regions of the northeastern United States including Maine, where several salmon rivers have been listed as endan-gered (Magee et al, 2001(Magee et al, , 2003; National Academy of Science, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The specific threats identified as contributing to the sedimentation, fragmentation and water quality indices are very interesting from a recovery planning perspective, and contradict some current perceptions. It is generally accepted that pH has an extremely large influence on Atlantic salmon in the Southern Upland, where increases in acid precipitation from the 1950s have been implicated in population extirpations and severe population decline (Watt et al 1983;Lacroix 1989). However, the influence of past mining activities on current water quality has never been identified as a pressing issue for mitigation, although it has been identified as a potential threat (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, agricultural activities, industrial sites (like gravel quarries) and roads are considered to be chronic sources of sediments (Gilvear et al 2002), where increased sedimentation has been linked to reduced habitat quality for salmonids as well as to acute mortality of eggs or juveniles (Soulsby et al 2001;Julien and Bergeron 2006), particularly during storm events (Lisle 1989). Furthermore, the bedrock geology of the Southern Upland region has little buffering capacity (Watt et al 1983;Korman et al 1994), which makes Southern Upland salmon particularly vulnerable acid deposition from either precipitation or land-based sources (Farmer et al 1980;Watt 1987). Atmospheric deposition in the form of acid rain has substantially reduced pH in many rivers throughout the Southern Upland (Watt 1987).…”
Section: Part 3: Identification Of Variables Contributing To Threats mentioning
confidence: 99%
“…Firstly, many lakes are influenced by sea-spray (Watt et al, 1983), which though neutral overall in terms of acidification, can cause temporary imbalances in ANC and acidity (Heath et al, 1992); these must be taken into account when modelling water chemistry. Secondly, the abundance of wetlands in this region causes high concentrations of natural organic acids (NOAs) that can reduce pH in these waters (Clair and Freedman, 1986).…”
Section: Introductionmentioning
confidence: 99%